The effect of pressure and temperature on the microstructure and mechanical properties of polycrystalline graphites - Van der Riet, Clement David (Centre for Materials Engineering, 2016)
A study has been made of the effects of combinations of pressure and temperature ori six polycrystalline, synthetic graphites, in the high pressure domain (> 1 GPa).The graphites were investigated in three different conditions: (1) the "as received" condition (AR condition),(2) after exposure to pressures of about 3 GPa at room temperature (in a piston-cylinder device – PC condition) and (3) after exposure to temperatures of about 1500°C at pressures of about 5.5 GP a (high temperature- high pressure, or HTHP, condition). Their microstructures have been compared on the basis of X-ray diffraction measurements to determine their crystallite sizes (L˳ and L˳), interplanar spacings (c and a) and textures. Optical and scanning electron microscopy were used to examine their fracture surfaces and macro porosity. Mercury porosimetry provided a means of establishing the pore size distribution of pores of less than 20 1-1m diameter. Bulk and skeletal densities were determined from mercury porosimetry and helium pycnometry respectively. The effects of PC and HTHP conditioning on their mechanical properties, were measured by both uniaxial compression fracture tests, and by electrical resistivity measurements. In addition, the triaxial behavioursof the six graphites in the AR condition were evaluated from piston-cylinder compression tests. All the isopressed graphites were found to have very similar crystallite sizes, interplanar spacings and textures in the AR condition. The extruded graphite had larger crystallite dimensions, and was slightly less isotropic, than the other grades. Fracture occurred due to cleavage of the basal planes of crystallites in the filler particles or binder. The size, shape and orientation of filler particles and porosity with respect to the applied stress field determined whether fracture was intergranular, or trans granular, in nature. Limited basal plane slip and sub-critical microcracking caused uniaxial compressive stress-strain curves typical of those of polycrystalline graphites,i.e. convex with respect to the strain axis. Fracture strengths and strains were related to the proportion of amorphous, intercrystallite bonding and, to a lesser extent, to porosity.